The health MDGs in Zanfara state with emphasis on maternal mortality 2010-2015: perspectives and challenges - Mohammed Maiwada, Abdullahi; A. Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mamat, Nik Mazlan; A-Baba, Tukur (Institute of Development Administration of Nigeria, 2015)
The Nigerian government has demonstrated commitments for the attainment of the Millennium Development Goals particularly the Health MDGs with an emphasis on reducing maternal mortality. Yet Nigeria along with other developing countries especially in Sub-Saharan Africa could not achieve most the health related targets. Maternal mortality is still unacceptably high with Nigeria contributing to about more than 10% of the global burden of maternal deaths at 576/100.000 live births. Nothern Nigeria continued to have the highest maternal mortality ratio compared to the south states of the country. Zamfara State has one of the highest rates in the northwest second next to Kano State. This study aims to examine some of the challenges of achieving the health MDGs targets in Zamfara State with a particular reference to maternal deaths in the states. Data for this study were collected through qualitative method facilities based approached and review of secondary data. The results of the study showed high maternal deaths at the health facilities and low hospital utilization and health facility deliveries. The causes for high maternal deaths are both direct medical and indirect causes. Some of the medical causes include Hemorrhage, eclampsia sepsis and malaria, while the indirect and non medical causes include socio-cultural and economic factors. These are some of the challenges faced in achieving the MDG target of reducing maternal deaths in Zamfara State. With the new UN Sustainable Development Goal (SDGs). States in the north like Zamfara needs to re-strategize efforts to improve on the health SDGs especially the maternal health.